Advisory Laporan Keuangan dan Taxation untuk Peningkatan Kepatuhan Perpajakan - Adrie Putra; M.F Arrozi Adhikara; Sugiyanto Sugiyanto; Jatmiko Jatmiko (Abdimisi, 2021)
Preparation of financial reports, as a tool for analyzing financial performance that can provide information about financial position, as well as filling and reporting of Annual Income Tax Returns for Individual Taxpayers requires special attention for all tax objects, whereas taxpayers are obliged to calculate and deposit taxes, as well as fill and report the Annual Personal Income Tax Return (OP) no later than March 31st of the following year.The purpose of this Community Service (PKM) is to provide assistance to employees of all taxpayers and partners in preparing financial reports as well as filling and reporting the Annual Income Tax Return for Individual Taxpayers 1770 SS using e-filing. This is in order to provide a solution for the tax object for partners to carry out their obligations as individual taxpayers. The output target to be achieved is to be included in the national proceedings as a presenter. The method used in this activity is the material training method, namely the preparation of basic financial reports using basic applications and filling and reporting of the 1770 SS Annual Income Tax Return for Individual Taxpayers using e-filing. The implementation of this activity is recorded in a learning video and softcopy of the material to the participants